E-government sebagai solusi reformasi terciptanya good governance - Dharmawan, Eka Wira; Warsono, Hardi; Kismartini, Kismartini; Astuti, Retno Sunu (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The growing digital era has forced the world to keep up with it. Various aspects of people's lives are now connected to digitalization. In recent years, Indonesia has begun to implement e-government development. This period of political reform, which began in 1997, began to break down the arrogance of the bureaucracy and gave rise to an independent society. People began to demand improvements in bureaucratic performance towards the public in various countries, including Indonesia, which is required to provide e-government services that are considered more effective and efficient for the community. This research uses a descriptive qualitative approach with a literature study method. The results obtained are that in implementing e-government in Indonesia there are several things that need to be considered such as government interaction with the community, the level of effectiveness and efficiency. In Indonesia itself, the application of e-government to support good governance, one of which is e-procurement, which is a process of procuring goods and services that are presented on the website so that it is more transparent.